2021
DOI: 10.1097/pr9.0000000000000912
|View full text |Cite
|
Sign up to set email alerts
|

Telehealth and chronic pain management from rapid adaptation to long-term implementation in pain medicine: A narrative review

Abstract: Telehealth services for chronic pain management are a vast new field with many potential applications for providing high quality, patient-centered care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
51
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 47 publications
(53 citation statements)
references
References 34 publications
2
51
0
Order By: Relevance
“…They felt that they needed to adapt their practices for tele-assessments, including less reliance on their own observations and heavier reliance on supplementary sources of information and parents for child assessments. Research has consistently shown that adaptations of clinical practices are required to support clients or patients via telehealth ( Malandraki, Arkenberg, Mitchell, & Malandraki, 2021 ; Waller et al, 2021 ), and assessments for some conditions such as chronic pain require additional involvement from the clients or patients (e.g., Perez, Niburski, Stoopler, & Ingelmo, 2021 ). A number of specific challenges related to telehealth delivery for autism assessments were identified by clinicians, including administration difficulties with eye contact being most challenging to assess.…”
Section: Discussionmentioning
confidence: 99%
“…They felt that they needed to adapt their practices for tele-assessments, including less reliance on their own observations and heavier reliance on supplementary sources of information and parents for child assessments. Research has consistently shown that adaptations of clinical practices are required to support clients or patients via telehealth ( Malandraki, Arkenberg, Mitchell, & Malandraki, 2021 ; Waller et al, 2021 ), and assessments for some conditions such as chronic pain require additional involvement from the clients or patients (e.g., Perez, Niburski, Stoopler, & Ingelmo, 2021 ). A number of specific challenges related to telehealth delivery for autism assessments were identified by clinicians, including administration difficulties with eye contact being most challenging to assess.…”
Section: Discussionmentioning
confidence: 99%
“…It has been also debated, that with the development of the technologies, the pain management, diagnosis and therapy can be virtually implemented with use of high definition 3D, 3D holograms which can be touched, felt and behave, augmented reality options etc. [35] Study by Bikson et al discussed the advancements in tele-neuromodulation following the pandemic. Tele-neuromodulation has been considered as a promising course of novel therapeutic solutions for patients with limited accessibility to the services based on mobility, location, financial issues etc.…”
Section: Disease-specific Telemedicine Research and Considerationsmentioning
confidence: 99%
“…The rapid adaptation of telemedicine in child neurology care due to the COVID-19 pandemic has been assessed in several studies, 13,15,[20][21][22][23][24][25] but beyond the initial implementation, the impact on care had not been fully assessed. Analyzing trends of telemedicine, a heterogeneous picture emerges with regards to patients suitable for telemedicine care and the effects of health disparities.…”
Section: Discussionmentioning
confidence: 99%